Human resources management in public administration: a case study in the Government of Mato Grosso (Brazil) (Gestão & Regionalidade, 2016)
The purpose of this article is to evaluate the perception of public agents regarding the quality of the roles played by the HumanResources (HR) field. For this purpose, a descriptive survey research with 332 public agents of middle fields of the stategovernment of Mato Grosso was performed. Data were collected in a single period and evaluated with descriptive statisticsmeasurements and analysis of variance. Data analysis indicates that there are no significant differences between the meansof evaluation of HR roles in the state government of Mato Grosso and the means found by research in private companies.The results show the need for HR to establish greater coherence between their self-image and the expectations and needsof servers regarding services rendered by the area.